Peran Perempuan Dalam Membangun Pemerintahan Desa Ciseeng - Nur Hikmawati; Elfira Zulfani Salsabila (Jurnal Relasi Publik, 2024)
The role of women in building village government is very important, because they contribute to the economic, social and environmental sectors. Women also have a key role in managing natural resources, local economic activities and maintaining environmental sustainability to build strong social networks in village communities. Women’s involvement is an absolute requirement in efforts to realize village development as an independent village. It is impossible for a country to prosper if its women are left behind. The complete and comprehensive development of a country requires the full role of women in all areas of life. Women as citizens or as sources of village development have the same rights, obligations and opportunities as men in all development activities in the country. All life. The role of women has also been accommodated by all national development regulations, such as Law no. 6 of 2014 concerning Villages, which states that women’s involvement is very necessary for village development. With the existence of women in Ciseeng Village, which is the location of this research, most residents here position women as equal to men. This means that women can also hold government positions ranging from BPD, Village Apparatus, to Village Head. In Ciseeng itself, the role of women in all aspects of development is quite pronounced, starting from participating in building village facilities, maintaining village security, PKK in empowering families, and so on.